Transformative Education: Emphasizing 21st Century Skills and Competencies in The Independent Learning Curriculum - Anwar, Saeful; Umam, Hoerul (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to comprehensively investigate the implementation of the 21st-century independent learning curriculum, with a specific focus on critical thinking literacy, life skills, and mastery of tools for work. A qualitative research approach was employed, enabling in-depth description and elaboration of the implementation process and educational competencies associated with 21st-century learning. Data collection for this study was conducted through a thorough analysis of relevant literature sources, utilizing library research as the primary method. The research findings demonstrate that the implementation of the independent learning curriculum (KMB) within the context of 21st-century education represents a viable and promising approach to enhance the overall quality of learning in educational institutions. Through the strategic implementation of KMB, educators can effectively facilitate a more interactive, enjoyable, and efficient learning environment, thereby fostering meaningful educational experiences for students. Furthermore, KMB proves instrumental in nurturing students' ability to engage in autonomous learning, collaborative endeavors, and the cultivation of critical and creative thinking capacities